If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) = 3(x + -1) Reorder the terms: 2(-5 + x) = 3(x + -1) (-5 * 2 + x * 2) = 3(x + -1) (-10 + 2x) = 3(x + -1) Reorder the terms: -10 + 2x = 3(-1 + x) -10 + 2x = (-1 * 3 + x * 3) -10 + 2x = (-3 + 3x) Solving -10 + 2x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -10 + 2x + -3x = -3 + 3x + -3x Combine like terms: 2x + -3x = -1x -10 + -1x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 -10 + -1x = -3 + 0 -10 + -1x = -3 Add '10' to each side of the equation. -10 + 10 + -1x = -3 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -3 + 10 -1x = -3 + 10 Combine like terms: -3 + 10 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) | | -4(x+8)=-3x-5 | | 4(y+5)=-6(2y-1)+4y | | x^2+8x+8=o | | -5x=5x-100 | | 0.8x+.06(x+9)=1.24 | | 8w-33=-5(w+4) | | 102=-5(3-5m) | | -6=18k | | 18=4(2+x)-15 |